Erenumab versus topiramate for the prevention of migraine – a randomised, double-blind, active-controlled phase 4 trial. (February 2022) - Reuter, Uwe; Ehrlich, Marc; Gendolla, Astrid; Heinze, Axel; Klatt, Jan; Wen, Shihua; Hours-Zesiger, Peggy; Nickisch, Jacqueline; Sieder, Christian; Hentschke, Christian; Maier-Peuschel, Monika
Background: We compared the tolerability and efficacy of erenumab, a monoclonal antibody binding to the calcitonin gene-related peptide receptor, to topiramate for migraine prophylaxis in adults. Methods: HER-MES was a 24-week, randomised, double-blind, double-dummy, controlled trial conducted in 82 sites in Germany. Patients with ≥4 migraine days per month and naïve to study drugs were randomly assigned (1:1) to either subcutaneous erenumab (70 or 140 mg/month) plus topiramate placebo (erenumab group) or oral topiramate at the individual dose with optimal efficacy (50–100 mg/day) plus erenumab placebo (topiramate group). The primary endpoint was medication discontinuation due to an adverse event during the double-blind phase. The proportion of patients that achieved ≥50% reduction from baseline in monthly migraine days during the last 3 months of the double-blind phase was a secondary endpoint. Results: Seven hundred and seventy-seven patients were randomised (from 22 February 2019 to 29 July, 2020) and 95.1% completed the study. In the erenumab group, 10.6% discontinued medication due to adverse events compared to 38.9% in the topiramate group (odds ratio, 0.19; 95% confidence interval 0.13–0.27; p < 0.001). Significantly more patients achieved a ≥50% reduction in monthly migraine days from baseline with erenumab (55.4% vs. 31.2%; odds ratio 2.76; 95% confidence interval 2.06–3.71; p < 0.001). No new safety signals occurred. Conclusions: Erenumab demonstrated a favourable tolerability and efficacy profile compared to topiramate. Trial registration: ClinicalTrials.gov NCT03828539, URL:https://clinicaltrials.gov/ct2/show/NCT03828539